2020
DOI: 10.1186/s43055-020-00352-6
|View full text |Cite
|
Sign up to set email alerts
|

Arterial spin labeling in the grading of brain gliomas: could it help?

Abstract: Background Gliomas are characterized by high morbidity and mortality with low cure and high recurrence rates, which depends to a great degree on the angiogenesis of the tumor. Assessment of such angiogenesis by perfusion techniques is of utmost importance for the preoperative grading of gliomas. The purpose of this study was to assess the role of arterial spin labeling (ASL) perfusion as a non-contrast MRI technique in the grading of brain gliomas, in correlation with the dynamic susceptibility contrast perfus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…In another meta-analysis, although not only composed of gliomas, normalized cerebral blood flow derived from ASL perfusion had 83% accuracy in separating low and high-grade pediatric brain tumors (111). Other authors have also confirmed that ASL can be a potentially valuable tool to differentiate low from high-grade tumors (106,(111)(112)(113)(114) and that the technique has comparable results with DSC in the differentiation between low and HGGs (115).…”
Section: Arterial Spin Labeling (Asl) Perfusionmentioning
confidence: 87%
“…In another meta-analysis, although not only composed of gliomas, normalized cerebral blood flow derived from ASL perfusion had 83% accuracy in separating low and high-grade pediatric brain tumors (111). Other authors have also confirmed that ASL can be a potentially valuable tool to differentiate low from high-grade tumors (106,(111)(112)(113)(114) and that the technique has comparable results with DSC in the differentiation between low and HGGs (115).…”
Section: Arterial Spin Labeling (Asl) Perfusionmentioning
confidence: 87%
“…Finally, the maximum value of tumor ROI was divided by the mean value of contralateral normal gray matter ROI to estimate CBF ratios 29,38,39 …”
Section: Methodsmentioning
confidence: 99%
“…If the delay time is sufficiently long for the water spins to reach the capillary bed or tissue, ASL signal is directly proportional to CBF, and absolute CBF measurements can be calculated. Studies have shown the role of ASL in neuro‐oncology for the diagnosis, grading and therapy monitoring of gliomas, with results comparable to those of conventional DSC 25–29 . However, the potential of ASL to assist in the intraoperative setting has been scarcely explored.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various studies have been conducted to evaluate the role of ASL derived tumour blood flow for both tumour grading/differentiation and treatment response with some promising results [ 42 , 43 , 44 , 45 , 46 ]. Some authors have suggested that ASL may be more sensitive in distinguishing tumour recurrence and pseudoprogression than other, more invasive techniques [ 44 , 47 ].…”
Section: Biological Imagingmentioning
confidence: 99%